2016
DOI: 10.1016/j.jor.2016.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity pulsed ultrasound in the treatment of long bone nonunions: Evaluation of cytokine expression as a tool for objectifying nonunion therapy

Abstract: Our findings suggest that LIPUS does not lead to a significant increase in cytokine levels in patients with nonunions. It is likely that "successful" treatment can be attributed to spontaneous healing. Our results suggest that LIPUS is not a proper treatment for long bone nonunions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(71 reference statements)
0
3
0
3
Order By: Relevance
“…Low-intensity pulsed ultrasound (LIPUS) has generally been recognized that the micromechanical strains generated by high-frequency acoustic pressure waves evoke biochemical events that can regulate fracture healing [ 11 ]. Many studies have demonstrated that LIPUS stimulation produces significant multifunctional effects on bone formation and resorption [ 12 , 13 ]. It has been reported that LIPUS can stimulate fracture healing and has been used to treat bone defects in clinical therapy [ 14 , 15 ], and also accelerates bone maturation in distraction osteogenesis cases in animal models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low-intensity pulsed ultrasound (LIPUS) has generally been recognized that the micromechanical strains generated by high-frequency acoustic pressure waves evoke biochemical events that can regulate fracture healing [ 11 ]. Many studies have demonstrated that LIPUS stimulation produces significant multifunctional effects on bone formation and resorption [ 12 , 13 ]. It has been reported that LIPUS can stimulate fracture healing and has been used to treat bone defects in clinical therapy [ 14 , 15 ], and also accelerates bone maturation in distraction osteogenesis cases in animal models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the therapeutic potential of LIPUS and sonoporation is well recognized, the biological grounding in our current scientific understanding of these two phenomena has remained to be critically weak. In the case of LIPUS, its stimulatory benefits are sometimes controversial [10]- [12], and a stronger knowledge of the underlying biological mechanisms is necessary to corroborate the surmised therapeutic value [13], [14]. In the case of sonoporation, its practical efficiency is deemed to be mediocre [15], [16], and the pursuit of detailed knowledge on the pertinent cellular bioeffects is seemingly essential to devise strategies for improving the overall efficiency of this membrane perforation approach [17], [18].…”
mentioning
confidence: 99%
“…Studies 63 have shown that ultrasound increases cellular migration, 64 proliferation, and localized vascularization, reducing 65 inflammation and accelerating soft tissue healing [23, 66 24,26,27,28,29,30]. The Food and Drug Administra-67 tion (FDA) has approved ultrasound treatment systems 68 for non-union fracture healing, musculoskeletal pain, 69 and soft tissue injuries as a standalone or combination 70 therapy [31,32,33,34,35].…”
mentioning
confidence: 99%